Evaluation and identification of advanced inter-specific derivatives from crosses of Cicer arietinum with C. reticulatum and C. echinospermum for agro-morphological, quality traits and disease resistance - Vadithya, Amool Singh; Singh, Inderjit; Rani, Upasana; Venadan, Sreya; Jajoriya, Rajdeep; Singh, Mohar; Oberoi, Harpreet Kaur; Singh, Sarvjeet; Bharadwaj, Chellapilla; Bindra, Shayla (Frontiers in Plant Science, 2024)
Inter-specific hybridization is a key strategy in modern crop improvement, aiming to integrate desirable traits from wild species into cultivated backgrounds. This study delves into the evaluation and identification of advanced inter-specific derivatives (IDs) derived from crosses of cultivated chickpea with Cicer reticulatum and C. echinospermum. The primary aim was to incorporate desirable yield enhancement traits, disease resistance, and nutritional quality traits into cultivated chickpea. The IDs were assessed during rabi 2021-22 and 2022-23 in the northern plains zone of India. Significant amount of genetic variability was observed for key agro-morphological traits having high heritability and genetic advance. Superior derivatives were identified for early flowering, high seed yield, and resistance to Ascochyta blight, Botrytis grey mould, and Fusarium wilt. Significant variability for crude protein and total soluble sugar content was also observed among the derivatives. The findings highlight the potential of utilizing wild Cicer species to broaden the genetic base of cultivated chickpea for the development of robust, high-yielding, disease-resistant varieties with improved nutritional traits suitable for diverse environmental conditions. The superior derivatives identified in this study hold promise for future breeding programmes for improving productivity, disease resistance and nutritional quality.